Experimental study on the nonlimit active earth pressure of finite soil in proximity engineering - Zhenbo Zhang; Baosheng Qie; Fei Xu; Wenzheng Wang; Zhichun Liu; Xuebing Lin; An Huang (Scientific Reports)
Abstract This study focuses on the active earth pressure distribution of finite soil masses in urban proximity engineering, with a specific emphasis on nonlimit conditions. Through laboratory model tests, the relationship between the nonlimit earth pressure and displacement of the finite soil mass is investigated. Furthermore, the distribution law of the nonlimit earth pressure is explored, considering the influence of the existing structure, proximity distance, and soil cover thickness of the existing structure on the nonlimit earth pressure distribution within the finite soil mass. The findings indicate the following: (1) the distribution of the nonlimit active earth pressure along the depth of the retaining walls is nonlinear, exhibiting an initial increase, followed by a decrease near the bottom of the existing structure and then another decrease after an initial increase; (2) the nonlimit active earth pressure and ultimate active earth pressure of semi-infinite soil are greater than those of finite soil; (3) as the proximity distance increases, the nonlimit active earth pressure of finite soil gradually increases, and the rate of decrease in earth pressure at the existing structure floor decreases; (4) with increasing soil cover thickness of the existing structure, the nonlimit active earth pressure and ultimate active earth pressure of finite soil gradually increase, and the position of change along the depth of the retaining walls initially increases, then decreases, and finally continues to increase with increasing depth. The aforementioned research offers a foundation for determining the appropriate finite soil pressure in proximity engineering.